Timeliness Of Spp Payments At Smk Tritech Infomatika Using Naive Bayes Algorithm - Muhammad Fakhri; Rial Beimar Volado Sibuea; Tri Krisandi Silalahi (Yayasan Asmin Intelektual Berkah, 2023)
SMK Tritech Informatika is one of the vocational schools located on Jalan Bhayangkara Medan. Smk Tritech plays an important role in education. However, many schools are late in financing their operations. So there are many problems related to school operational payments such as tuition payments. SPP payment is an important problem at Smk Tritech Infomatika because many of the students are late in paying SPP even though the payment deadline has been set. Therefore, it is necessary to evaluate the SPP payment. To overcome this problem, it is necessary to detect the factors that cause late tuition payments using data mining. The data mining technique used is classification with the Naive Bayes algorithm method.